Studies in Mahayana G. C. Pande. - Werner, Karel (Buddhist Studies Review, 1997)
Studies in Mahayana G. C. Pande. (Prof. L. M. Joshi Commemmorative Lecture Series III), Central Institute of Higher Tibetan Studies, Sarnath, Varanasi 1993. xii, 179 pp. No price given. ISBN 81-900149-7-8 (hb), 81-900149-8-6 (pb).